Cryptocurrencies as a means of payment and Private International Law - Ruiz Rodríguez, Raúl (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The purpose of this study is the analysis of the legal nature of the so-called crypto-currencies or virtual currencies and of the positions defended by different authors based on the current normative state and the decisions issued by international authorities, with special emphasis on the conception of cryptocurrencies as a “means of payment” and “property”. In addition, an examination is also made of the adequacy of existing legal mechanisms in the field of private international law to deal with the consequences arising from such qualifications and of the possibility or need for legislative amendments to achieve satisfactory regulation of virtual currencies.